Ideologyas a factor of personal ethnic worldview transformation - Олександр Іваскевич (Київський національний університет імені Тараса Шевченка, 2015)
This study determined the ethno-cultural dimensions of Ukrainians worldview that allows forecasting the dynamic changes in value systems and their connections with the ideological influence of various actors on Ukrainian political space. There havebeenmarkedthe high level of individuality, tolerance for uncertainty,contextuallity,masculinityandidentify specific distance of power, characterized by lack of trust in the political authorities and negative attitude to them. This accentuation may be associated with the constant threat of integrity of Ukraine as a state,which exists throughout the existence of Ukraine, and Ukrainian ethnic worldview and can be related to the crisis taking place in Ukraine. According to this study, it is possible to form thenational ideology and mechanisms of its implementation. The map of Ukrainian ethnic worldview that can explain the social processes taking place in Ukrainian society should be used in order to forecast the implementation influence of ideology. Dynamic and controversial events of the modern world is the result of the crisis of globalization and the revival of world ideologies that require finding a qualitatively new practical ways to solve them. In the current political psychology, along with the problems of political leadership, management, psychology of terrorism, motivation and formation of beliefs, making political decisions remain unresolved the issue of ideological support in socio-political life of various geopolitical dimensions.

Динамічні та суперечливі події сьогодення є результатом кризи глобалізації та відродження світових ідеологій, що вимагають пошуку якісно нових практичних способів їх вирішення. У сучасній політичній психології поряд з проблемами політичноголідерства, керівництва, психології тероризму, мотиваціїта формування переконань, приймання політичних рішень, невирішеною лишається проблема ідеологічного забезпечення суспільно-політичного життя у різних геополітичних вимірах. У даному дослідженні проведено визначення етнокультурних вимірів світогляду українців, що дає змогу визначити, динаміку змін системи цінностей та їх зв'язок із поліідеологічним впливом різних акторів українського політичного простору. Було виявлено високий рівень індивідуальності,контекстуальності, маскулінності, а також виявлено особливу дистанції влади, що характеризується відсутністю довіри до органів влади та негативним ставленням до неї. Подібна акцентуація може бути пов'язана із постійною загрозою цілісності України як держави та українському етнічному світогляду, котра існує впродовж всього існування України та із кризою, що має місце в Україні. Відповідно до цього дослідження можливим стає формування державної ідеології та механізмів її запровадження. За результатами цього дослідження можна розглянути мапу етнічного світогляду українців, що пояснює соціальні процеси котрі відбуваються всередині українського суспільства.
Ідеологія як фактор трансформації етнічного світогляду особистості
Keywords: світогляд; ідеологія; етнопсихологічні виміри; worldview; ideology; ethnopsychological dimensions